Inhibition of Candida albicans Biofilm Formation by Farnesol, a Quorum-Sensing Molecule - Ramage, Gordon (American Society for Microbiology, 2002)
Farnesol is a quorum-sensing molecule that inhibits filamentation in Candida albicans. Both filamentation and quorum sensing are deemed to be important factors in C. albicans biofilm development. Here we examined the effect of farnesol on C. albicans biofilm formation. C. albicans adherent cell populations (after 0, 1, 2, and 4 h of adherence) and preformed biofilms (24 h) were treated with various concentrations of farnesol (0, 3, 30, and 300 μM) and incubated at 37°C for 24 h. The extent and characteristics of biofilm formation were then assessed microscopically and with a semiquantitative colorimetric technique based on the use of 2,3-bis(2-methoxy-4-nitro-5-sulfo-phenyl)-2H-tetrazolium-5-carboxanilide. The results indicated that the effect of farnesol was dependent on the concentration of this compound and the initial adherence time, and preincubation with 300 μM farnesol completely inhibited biofilm formation. Supernatant media recovered from mature biofilms inhibited the ability of planktonic C. albicans to form filaments, indicating that a morphogenetic autoregulatory compound is produced in situ in biofilms. Northern blot analysis of RNA extracted from cells in biofilms indicated that the levels of expression of HWP1, encoding a hypha-specific wall protein, were decreased in farnesol-treated biofilms compared to the levels in controls. Our results indicate that farnesol acts as a naturally occurring quorum-sensing molecule which inhibits biofilm formation, and we discuss its potential for further development and use as a novel therapeutic agent.